Preliminary Assessment of Acute and 28-Day Repeated Dose Oral Toxicity of a Newly Developed Herbal Mixture on Experimental Animal - Darbar, Soumendra; Saha, Srimoyee; Pramanik, Kausikisankar; Chattopadhyay, Atiskumar (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: Toxicity is an expression of being poisonous, indicating the state of adverse effects led by the interaction between toxicants and cells. The present study was designed to evaluate the acute oral toxicity study and 28 days repeated toxicity study of Herbal Mixture (HM) according to OECD guidelines. Materials and Methods: In acute oral toxicity study, Herbal mixture was administered at 2000mg/kg orally and animals were observed for toxic signs at 30 min, 1, 2 and 4 hr and thereafter once a day for the next 14 days. In repeated dose-28-day toxicity study, the animals were divided into four groups of 6 animals each. Group-1 animals served as a control. Group II Animals received low dose of test drug 100 mg/kg (orally). Group III animals received middle dose of test drug 200 mg/kg (orally) once daily for 28 days respectively. Group IV animals received high dose of test drug 400 mg/kg (orally) once daily for 28 days respectively. Results: The study results showed that neither the acute toxicity study of herbal mixture at the dose level of 2000mg/kg nor the repeated dose study did not produce any toxic sign or mortality during study. In repeated dose toxicity study, no significant changes were observed in the haematological and biochemical parameters, relative organ weight, gross necropsy and histopathological examination with herbal mixture treatment. Conclusion: The results of the present study suggest that LD50 of newly developed Herbal Mixture (HM)>2000mg/kg and the mixture is completely safe and non-toxic for therapy.
Keywords: Acute oral toxicity; Sub acute toxicity; Herbal mixture; Haematology; Liver; function test; Histology